2000
DOI: 10.1128/iai.68.6.3523-3534.2000
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relatedness and Superantigen Expression in Group A Streptococcus Serotype M1 Isolates from Patients with Severe and Nonsevere Invasive Diseases

Abstract: The relatedness of group A streptococcal (GAS) strains isolated from 35 Canadian patients with invasive disease of different severity was investigated by a variety of molecular methods. All patients were infected with M1T1 strains and, based on clinical criteria, were classified as severe (n ‫؍‬ 21) and nonsevere (n ‫؍‬ 14) invasive GAS infection cases. All the M1 strains studied had the emm1.0 allele and the same streptococcal pyrogenic exotoxin (Spe) genotype, speA ؉ speB ؉ speC speF ؉ speG ؉ speH smeZ ؉ ssa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
233
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 249 publications
(241 citation statements)
references
References 38 publications
8
233
0
Order By: Relevance
“…7,61 The bacteria were incubated in THY, that is, Todd Hewitt Broth (DIFCO, Detroit, MI, USA) supplied with 1.5% of yeast extract (DIFCO), for 17 h, washed twice with sterile phosphatebuffered saline solution, PBS (Gibco, Carlsband, CA, USA), then diluted to the final inoculum size with sterile PBS. The original isolate had been aliquoted in THY stocks containing 15% glycerol (Sigma, St Louis, MO, USA) at À801C.…”
Section: Bacteria and Culture Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…7,61 The bacteria were incubated in THY, that is, Todd Hewitt Broth (DIFCO, Detroit, MI, USA) supplied with 1.5% of yeast extract (DIFCO), for 17 h, washed twice with sterile phosphatebuffered saline solution, PBS (Gibco, Carlsband, CA, USA), then diluted to the final inoculum size with sterile PBS. The original isolate had been aliquoted in THY stocks containing 15% glycerol (Sigma, St Louis, MO, USA) at À801C.…”
Section: Bacteria and Culture Mediamentioning
confidence: 99%
“…This human pathogen causes a wide variety of conditions ranging from sore throat to invasive life-threatening diseases (reviewed in Cunningham 6 ), and the same strain of pathogen leads to different outcomes in different individuals. 7 Our laboratory provided direct evidence that the highly polymorphic human leukocyte antigen (HLA) genes confer high risk or protection in rheumatic heart disease; 8 as well as in streptococcal toxic shock (STSS) and necrotizing fasciitis (NF). 9,10 In GAS sepsis, allelic variation in HLA class II molecules plays a major role in modulating infection severity, primarily because they serve as binding and signaling receptors for superantigens, 11,12 which are the primary trigger of the severe inflammatory responses that can lead to organ failure and shock.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas all GAS isolates examined thus far secrete one or more SAg, different strains can produce very different spectra of the Ͼ24 streptococcal SAgs. One of the most clinically relevant strains, the M1T1 strain, whose appearance coincided with the resurgence of severe streptococcal infections around the world in the 1980s, has the following SAg-encoding genes: speA, speF, speG, speJ, and SmeZ (9). SpeA, a horizontally acquired SAg, that has been recently introduced into this strain, has been shown to be a major player in the pathogenesis of STSS.…”
mentioning
confidence: 99%
“…Several studies have shown that host genetic factors are critical in determining host susceptibility against GAS infection [7][8][9][10]. Thus, while some individuals might respond to GAS infection with a mild disease, the same streptococcal strain can cause very severe invasive infection in more susceptible persons.…”
Section: Discussionmentioning
confidence: 99%
“…In the particular case of GAS, several studies have shown that individuals within a single human population vary genetically in their susceptibility to infection with this pathogen [7][8][9][10]. Thus, depending of the genetic makeup, different individuals will develop infections of different severities after encounter with the same streptococcal strain.…”
Section: Introductionmentioning
confidence: 99%